Valorisation: The case of the Faculty of Applied Sciences at the National University of Science and Technology, Zimbabwe - Ngwenya, S.; Boshoff, N. (South African Journal of Higher Education, 2018)
Valorisation is a process that adds value to academic knowledge. It comprises all activities pertaining to the dissemination and exploitation of such knowledge for social and economic benefit. A 4D valorisation map was generated for the National University of Science and Technology (NUST) in Zimbabwe, and specifically for the Faculty of Applied Sciences. The first three dimensions of the map are constants: actor (university), level of aggregation (faculty) and discipline (applied sciences). Quantitative and qualitative indicators were presented in the fourth dimension (stage), using three data sources: semi-structured interviews, Scopus publications and university documents. Results were organised according to the six stages of the fourth dimension: formulation of mission and policy (stage 1), agenda setting (stage 2), execution of research (stage 3), dissemination of results (stage 4), uptake and use of research (stage 5) and other interaction throughout the entire process (stage 6). The resultant valorisation map for NUST incorporated more qualitative (and often anecdotal) evidence than quantitative evidence. The university should keep records of dissemination and engagement activities for future mapping exercises.